The Development of Training Package on Counterfeit Gold Checking for Gold Shop Staffs - โอภาสบุตร, อภิศักดิ์; กอมณี, สุขมิตร; หกสุวรรณ, พงศ์ประเสริฐ (Journal of Educational Review Faculty of Education in MCU, 2019)
The purpose of this research were 1.To the development of training package on counterfeit gold checking for gold shop staffs have the 90/90 standard 2.To compare pre-test and post-test score 3.To study the satisfaction of gold shop staffs. The sample consisted of 10 gold shop staffs purposive sampling. The research instruments included a training package on counterfeit gold, practical test and satisfaction assessment form. The results indicated that the 1.Efficiency of the development of training package on counterfeit gold checking for gold shop staffs have the ๙๐/๙๐ standard were 91.50/ 90.00 according to the standard criteria set 2.Comparison of test scores before and after learn with training package shown that after learn with training package the post-test results were higher than that pre-test in the significance level of .05 according to the hypothesis 3.The satisfaction level of trainees to training package on counterfeit gold checking for gold shop staffs was high level.